Improving the Internal Combustion Engine Performance as a Driven Pump with a Modified Cooling System - E.S., Arbintarso; Muchlis, .; Miftahusaalam, .; S.S., Rahayu (INTI International University, 2022)
An irrigation system that uses a pump to channel water through pipes requires a stable pump performance influenced by the internal combustion engine's driving performance. The performance of an internal combustion engine is influenced by several things, one of which is the quality of the cooling system. The cooling system on the Yanmar TS190R diesel engine has a weakness with little cooling water, so it cannot be used continuously. The rice fields in Mojopuro Wuryantoro Wonogiri are rainfed rice fields, highly dependent on water supply through pumps in the dry season. The pump will work for a minimum of 10 days non-stop to irrigate 60 hectares of rice fields and require human resources to supervise around the clock. The research of the cooling system of the elevated water temperature was carried out on a Yanmar TS190R, water-cooled, diesel engine and Ebara 150 SQPB pump 15 kW, 2 m3/min capacity. The studies were conducted for the engine speed 500, 1000, 1500, 2000 rpm without circulation (initial) and with modified water cooling circulation. The flow rate of cooling water to the radiator depends on the pump's engine speed. A modified cooling system that combines a pump as a cooling water supply driven by an internal combustion engine can reduce the average radiator temperature from 96 to 76C. Lowering the radiator temperature allowed the diesel engine-pump system to operate for several days (more than ten days non-stop) without being supervised by workers.